Magnetron sputtered thin films and composites for automotive and aerospace electrical insulation - Hanby, Benjamin, V. T. (2019)
Ceramics are highly prised as insulating materials because of their high stability under demanding conditions (thermal, chemical and radiological). However, the use of ceramics as wire insulation is currently limited to powder packed and relatively thick low voltage coatings. This work follows the development of sputtered Al2O3 and Al2O3, SiO2 and Ta2O5 composite films as deposited onto copper. Copper disk studies will ultimately be translated onto Cu wire for a proof of concept study. Initial Al2O3 deposition utilised RF or DC sputtering but this found to have low deposition rate (up to 16 nmh 1) and to contain crystallite and metallic defects (up to 19.6 at. % Al0) respectively. These issues were addressed by introducing pulsed DC (PDC) deposition conditions, producing films with no crystalline or metallic defects (up to 146 nmh 1). The dielectric strength of PDC films measured by AFM time dependant dielectric breakdown was 310 ± 21 Vμm 1, higher than that of the DC deposited films which had a dielectric strength of between 165 ± 19 and 221 ± 20 Vμm 1. A dielectric strength of 310 Vμm 1 is suitable for applications with a voltage rating below 150 V and is also a good platform for the production of higher quality coatings. The mechanical properties of the films did suffer from a lower amount of blending at the interface, DC pull off strength was 25.8 ± 9.8 - 72.3 ± 5.6 MPa with the PDC pull off strength being 55.7 ± 2.9 MPa). Wires coated with such PDC Al2O3 showed promise with full circumference coating, however, short circuiting was apparent in the wires potentially caused by micro cracking induced either during or post deposition. The use of multilayer composites consisting of the aforementioned PDC Al2O3 and RF SiO2 or RF Ta2O5 resulted in significant gains with respect to the material’s electrical properties. The films deposited with 2 layers of each PDC Al2O3 and the RF addition performed best in terms of dielectric strengths of 513 ± 18 and 466 ± 86 Vμm 1 for Ta2O5 and SiO2 composites respectively. The success of the 2x2 layer configuration resulted from a compromise between the number of RF layers and their thickness. The mechanical properties did, however, suffer as a result of increased intrinsic stress caused by the use of multilayers of materials with varying expansion coefficients, reducing pull off adhesion strength to a maximum of 34.4 ± 4.4 MPa, where ideally the pull off adhesion would be above 80 MPa. Heat treatment of these coatings resulted in decreased adhesive properties, with a maximum pull off adhesion strength of 20.1 ± 0.9 MPa being apparent. Most of the electrical properties remained the same or were decreased by heat treatment, however the dielectric strength of the SiO2 composites improved by an average of 12 % resulting in a maximum dielectric strength of 517 ± 24 Vμm 1 due to a reduction in the defect density in the films. Conversely the electrical properties of Ta2O5 composites suffered greatly following heat treatment with a maximum dielectric strength of 358 ± 31 Vμm 1. This was theorised to result from Cu migration from the substrate and the potential for Ta2O5 to crystallise at temperatures close to 500 °C. Coating of Cu wires with PDC alumina was shown to be possible, with coatings of various interlayer and coating thickness. Characterisation showed that the wire coating rig enabled the whole circumference of the wire to be coated with alumina. Tensile testing resulted in transvers cracking followed by longitudinal cracking above an applied strain of 1.5 and 4.0 % respectively. Following heat treatment the copper substrate softened and resulted in delamination failures in the coatings during tensile testing. Electrical testing of the wires was inconsistent due micro cracking in the wire coatings. It has been shown that the use of mixed material composites sputtered by PDC and RF sputtering have potential as high dielectric strength insulating materials, improving upon the base Al2O3 believed to be a result of passivation of structural and compositional defects. Additionally, it has been shown that physical vapour deposition in conjunction with a modified sample holder can be utilised for coating of bare copper wire with the potential to act as isolative coatings.